Some characteristics of the uterine progestorone receptor and the effects of norethindrone on conception in the rock hyrax (Procavia capensis) - Van Aarde, Rudi J. (University of Pretoria, 2013)
Dissertation (MSc (Zoology))--University of Pretoria, 2006.